2011
DOI: 10.1371/journal.pone.0017976
|View full text |Cite
|
Sign up to set email alerts
|

Negative Impacts of Human Land Use on Dung Beetle Functional Diversity

Abstract: The loss of biodiversity caused by human activity is assumed to alter ecosystem functioning. However our understanding of the magnitude of the effect of these changes on functional diversity and their impact on the dynamics of ecological processes is still limited. We analyzed the functional diversity of copro-necrophagous beetles under different conditions of land use in three Mexican biosphere reserves. In Montes Azules pastures, forest fragments and continuous rainforest were analyzed, in Los Tuxtlas rainfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
148
2
24

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(186 citation statements)
references
References 34 publications
12
148
2
24
Order By: Relevance
“…However, we found no differences among study sites in FEve or FDis of dung beetle assemblages. Barragán et al (2011) similarly found that FEve and FDis remained the same among pastures, forest fragments and continuous rainforest and between small and large forest fragments. This lack of difference between the systems can be an indication that only the identity of traits (functional richness) is being influenced by the environment and not the structure of the functional assemblage (i.e.…”
Section: Functional Diversitymentioning
confidence: 72%
See 1 more Smart Citation
“…However, we found no differences among study sites in FEve or FDis of dung beetle assemblages. Barragán et al (2011) similarly found that FEve and FDis remained the same among pastures, forest fragments and continuous rainforest and between small and large forest fragments. This lack of difference between the systems can be an indication that only the identity of traits (functional richness) is being influenced by the environment and not the structure of the functional assemblage (i.e.…”
Section: Functional Diversitymentioning
confidence: 72%
“…Barragán et al, 2011). We calculated three indices of functional diversity for each study area: functional richness (FRic), functional evenness (FEve) and functional dispersion (FDis).…”
Section: Functional Diversitymentioning
confidence: 99%
“…These changes may occur due to different processes, and deforestation has been associated with decreases in functional diversity in different communities (Tilman et al, 1997;Dolédec et al, 2006;Flynn et al, 2009;Barragán et al, 2011). The consequences of these changes can be dramatic, especially in areas of high biodiversity, such as the Amazon (Barletta et al, 2010), one of the most important biomes of the planet due to the extent of its rainforests and drainage network (Krusche et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Esta información proporciona conocimiento valioso acerca de su dinámica y estabilidad frente a perturbaciones (Petchey & Gaston, 2006). Barragán et al, (2011), en referencia a comunidades de escarabajos copro-necrófagos, indican que la diversidad funcional se puede estimar basándose en la relocalización del alimento, el tamaño del escarabajo, el periodo de actividad diaria y la preferencia del alimento. En este estudio, se determinó emplear la preferencia del alimento de las especies de Scarabaeoidea, considerando los gremios alimentarios como los grupos funcionales (Rivas-Arancibia et al, 2014;Castañeda-Osorio et al, 2015;García-Martínez et al, 2015).…”
Section: Discussionunclassified